Compression Device-Assisted Extracorporeal Cardiopulmonary Resuscitation Cannulation in Pediatric Patients—A Simulation Study. Issue 3 (May 2022) - Peer, Syed Murfad; Bukhari, Syed; Desai, Manan; Tongut, Aybala; Ho, Anthony; Yerebakan, Can; Ramakrishnan, Karthik; Sinha, Pranava; Jonas, Richard A.; Yurasek, Greg; Cleary, Kevin
Background: Surgical neck cannulation for pediatric extracorporeal cardiopulmonary resuscitation (ECPR) requires multiple interruptions of manual chest compressions to facilitate the procedure. Effective uninterrupted CPR is essential to prevent neurological injury. We hypothesized that an automated chest compression device can be used to provide effective and uninterrupted chest compressions during pediatric neck ECPR cannulation. The feasibility of surgically cannulating the right carotid artery and right internal jugular vein in an infant during ongoing automated chest compressions was tested in a simulation study.Methods: A working prototype of a pediatric chest compression device was designed to provide automated chest compressions on an infant CPR manikin at the rate of 120 compressions/minute. A feedback device attached to the manikin was used to monitor the effectiveness of CPR. A synthetic artery, vein along with carotid sheath and skin was utilized to simulate surgical neck exploration. ECPR simulation was conducted using the compression device to provide chest compressions.Results: Four ECPR simulations were conducted during which vessel sparing (n = 2) and non-vessel sparing (n = 2) cannulation of the right internal carotid artery and right internal jugular vein were performed during ongoing mechanical chest compressions. All four cannulations were successfully performed without the need to interrupt chest compressions.Conclusions: In a simulated environment, pediatric ECPR neck cannulation with uninterrupted chest compressions may be accomplished using an automated chest compression device. The strategy of compression device-assisted ECPR cannulation requires further study and could potentially reduce the neurological complications of ECPR.